Design and Development of SysPK: A Web-Based System for Managing Audit Documents - Azman, Azmeera Asfarina; Mohd Rusli, Nur Liyana; Awang, Hapini; Che Mohamed Arif, Ahmad Suki; Mansor, Nur Suhaili; Mohd Salim Lim, Nurulhuda; Ling, Koh Shiau (Multidisciplinary Applied Research and Innovation, 2023)
The method of audit document submission has become a major concern for the officers in Pejabat Pendidikan Daerah Cameron Highlands (PPDCH). Currently, the PPDCH officers use email to send documents to be reviewed by PPDCH internal lead auditor which is difficult because some documents sent via emails could be missed. Besides, it is considered inconvenient and risky, particularly when confidential documents are involved. Moreover, the documents need the feedback status or approval from the head officers before could be audited. Thus, the PPDCH proposed the development of a system that would make document management and record-keeping easier which allows secure document retrieval and could improve work productivity. Hence, the “Sistem Penarafan Kecemerlangan” (SysPK) is developed and aims to provide an online document management system for PPDCH. SysPK is developed to manage audit documents and will be used by officers in PPDCH. This system is an online web application. The auditors and PPDCH officers can submit the documents and check the status, whether being checked or not. In addition, the PPDCH will be able to view and give feedback on the submitted documents. The design and development of the web system followed the waterfall development methodology. First, the requirements were gathered through an online interview with the officer of PPDCH. Then a SysPK prototype had been developed based on the gathered requirement and a field study was carried out to evaluate the usability of the prototype. The results of the evaluation revealed that SysPK is useful and easy to use. The respondents are satisfied with the functions of managing documents provided by the SysPK. The study contributes towards an improvement of the previous method of managing, gathering and checking documents. The implementation of SysPK could improve the quality of managing documents while retaining the same process of workflow.